PENGARUH PERUBAHAN PENDAPATAN DAN PENYERAPAN TENAGA KERJA TERHADAP BERDIRINYA TERMINAL BAHAN BAKAR MINYAK (TBBM) PT. PERTAMINA (PERSERO) DI DESA REMEN KECAMATAN JENU KABUPATEN TUBAN - Amminullah Dwi Wilaga; Muhammad Sri Wahyudi Suliswanto (Jurnal Ilmu Ekonomi JIE, 2018)
The purpose of this study is to determine the effect of changes in income and employment that occurred in Remen Village community and to know whether there are differences in income levels after and before the Petroleum Fuel Terminal (TBBM) PT. Pertamina (Persero). The analytical tool used is to use a different test (t test) with the SPSS application. The result of the research by using different test (t test) indicating that there is change of income of Remen Village community before and after existence of Petroleum Fuel Terminal (TBBM) PT. Pertamina (Persero). Income differences between after and before the existence of Fuel Oil Terminal (TBBM) PT. Pertamina (Persero) where the average income of masrayakat before TBBM is Rp. 1.892.857 increased to Rp. 2.507.412 This means that every average community experienced an increase of 20.91% and did not affect the absorption of manpower but gave effect to new business opportunity for Remen Village community.Keywords: Fuel Oil Terminal, Revenue Changes, Labor.